Student disciplinary proceedings in universities: The importance of due process and evidentiary standards when investigating and adjudicating serious offences - CHEN, Siyuan (Institutional Knowledge at Singapore Management University, 2022)
In Singapore, recent news about university students involved in sexual offences have generated considerable discourse on the features of its criminal justice system, with a pronounced focus on the appropriate sanctions that should have been meted out by either the university or the courts/police. What might have been overlooked, however, is the question of maintaining due process and evidentiary standards, particularly in relation to the role of universities when they conduct their internal disciplinary proceedings for students alleged to have committed serious criminal offences. But what is happening in Singapore is not anomalous; universities across the world are increasingly confronted with allegations of crime, and the maintenance of procedural standards cannot be said to have been consistent or robust. This article therefore identifies some areas that warrant particular attention and exhorts universities to be mindful of not using two wrongs to make a right. It is hopefully of broad interest to universities worldwide, seeing as it draws from the disciplinary rules found in the full spectrum of tertiary institutions in jurisdictions such as Hong Kong, the UK, and Australia. In the author’s view, it should not be controversial to maintain a certain universality of standards as certain due process and evidentiary standards have long withstood the test of time, across geographical boundaries. A shift of sympathy to victims should not necessarily entail the compromise of fairness, and indeed, common sense.